Case report: Exceptional disease progression in a 70-year-old patient: generalized melanosis and melanuria in the course of metastatic melanoma - a case study - Calik, Jacek; Dzięgiel, Piotr; Sauer, Natalia (Frontiers in Oncology, 2024)
This case study documents an extraordinary disease progression in a 70-year-old patient diagnosed with metastatic melanoma. The patient's condition advanced to an unusual manifestation characterized by generalized melanosis and melanuria, a rare and foreboding complication of metastatic melanoma. The clinical presentation involved rapid-onset skin darkening, primarily affecting the face and torso, along with darkened urine, marking the onset of melanuria. Despite extensive diagnostic evaluations, including abdominal ultrasound, neck ultrasound, thoracic CT scans, and endoscopic examinations, the exact metastatic sites remained elusive, demonstrating the diagnostic challenges associated with this condition. Laboratory tests revealed abnormal hematological and biochemical markers, along with elevated S100 protein levels, indicating disease progression. The patient underwent a surgical skin biopsy that confirmed the diagnosis of metastatic melanoma, leading to a multidisciplinary approach to treatment. Following this, the patient-initiated chemotherapy with dacarbazine (DTIC). Regrettably, this was necessitated by the absence of reimbursement for BRAF and MEK inhibitors as well as immunotherapy, and it subsequently led to rapid disease progression and a decline in the patient's clinical condition. The patient's condition further complicated with erysipelas and increased distress, ultimately leading to their unfortunate demise. This case highlights the aggressive nature of generalized melanosis, characterized by a rapid clinical course, substantial pigmentation, and limited response to conventional chemotherapy. Importantly, the patient had a BRAF mutation, emphasizing the urgency of exploring alternative treatment strategies. Patients with a BRAF mutation are excellent candidates for BRAF and MEK inhibitor treatment, potentially allowing them to extend their lifespan if this therapy were available. The challenges encountered in diagnosing, managing, and treating this aggressive form of metastatic melanoma underline the need for early detection, tailored therapeutic approaches, and ongoing research efforts to improve patient outcomes in such cases.